Changes in the Composition of Aroma and Phenolic Compounds Induced by Different Enological Practices of Croatian White Wine - Marina Tomašević; Klemen Lisjak; Andreja Vanzo; Helena Baša Česnik; Leo Gracin; Natka Ćurko; Karin Kovačević Ganić (Polish Journal of Food and Nutrition Sciences)
The aim of this research was to investigate the effects of pre-fermentative maceration, Saccharomyces and non- Saccharomyces yeasts during alcoholic fermentation, and antioxidant additions (sulfur dioxide and glutathione) at bottling on the compositions of aroma and phenolic compounds of white wine Pošip ( Vitis vinifera L.). Additionally, for the first time the insight in volatile thiol precursors in Pošip grape was given, wherein higher concentrations of glutathionylated thiol precursors in comparison to cysteinylated ones were determined. Regarding the applied practices, significant differences among produced wines were established: pre-fermentative maceration resulted in a decrease of 3-sulfanylhexyl acetate (3SHA) and a slight increase of C6 compounds; indigenous yeasts produced higher concentrations of terpenes and esters, while sequential fermentation with Torulaspora delbrueckii also influenced higher concentrations of esters. Most abundant phenolic compound was caffeic acid, except for wine produced by indigenous yeasts where trans-caftaric acid was predominant. Finally, combination of higher SO2 and glutathione resulted in higher concentrations of thiols.